Investigation of the Microstructural Evolution and Mechanical Properties of the AlCoCrFeNi[sub.2.1] EHEA Fabricated by Additive Manufacturing Assisted by Heat Treatment - Zhang, Xin; Feng, Wenxin; Jia, Fanghui; Liu, Wanhui; Wang, Jian; Zhu, Lisong; Cai, Yangchuan (Materials, 2025)
Eutectic high-entropy alloys (EHEAs) exhibit excellent casting properties and comprehensive mechanical performance, making them suitable for fabricating spatial engineering components using additive manufacturing techniques. However, the rapid solidification process also leads to increased internal stress and reduced structural stability in the components. Therefore, this study focuses on the AlFeCoCrNi[sub.2.1] EHEA as the research subject, utilizing laser additive manufacturing to fabricate components and systematically investigating the influence of heat treatment processes on the microstructure and mechanical properties of the components. The research demonstrates that low-temperature heat treatment (700 °C and below) acts as a stress relief-annealing process for the components. The yield strength decreased from 1003.2 MPa to 742.1 MPa. At 900 °C heat treatment, the constraining effect between recrystallized grains and surrounding grains outweighs the dislocation release effect caused by recrystallization, resulting in an increase in dislocation density. The yield strength remained approximately stable at around 730 MPa. High-temperature heat treatment (1100 °C) alters the orientation of phase structures and fragments the two-phase structure through recrystallization, leading to generally stable mechanical properties of the components. The yield strength of the cast components further decreased to 582.6 MPa, while that of the LMD-fabricated parts retained stability at approximately 730 MPa.